2019
DOI: 10.1002/pon.5078
|View full text |Cite
|
Sign up to set email alerts
|

Association between anxiety, depression, and comorbid chronic diseases among cancer survivors

Abstract: Objective Cancer survivors (CSs) often face the dual physical burden of cancer and other comorbid chronic disease (CCD) and have a great deal of psychological distress, such as anxiety and depression. However, the association between CCD and psychological problems remain less clear in CS. This study was performed to investigate the prevalence of anxiety and depression in Chinese CS, and whether CCD have impact on CSs' anxiety and depression. Methods A cross‐sectional study was conducted among 1546 CSs in Shang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
4
26
1
1
Order By: Relevance
“…A 2019 paper authored by Yan et al performed a similar analysis, but investigated depression and multimorbidity in survivors of all cancer types as opposed to a specific focus on people with breast cancer [ 26 ]. They found that cancer survivors with 1–2 chronic comorbidities had greater risk of depression and there was also an additional association between comorbidities and anxiety, with patients with 3 or more comorbidities having 3.39 times the odds of anxiety compared to those without any comorbidity [ 26 ]. This study was limited to the population of Shanghai, China.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 paper authored by Yan et al performed a similar analysis, but investigated depression and multimorbidity in survivors of all cancer types as opposed to a specific focus on people with breast cancer [ 26 ]. They found that cancer survivors with 1–2 chronic comorbidities had greater risk of depression and there was also an additional association between comorbidities and anxiety, with patients with 3 or more comorbidities having 3.39 times the odds of anxiety compared to those without any comorbidity [ 26 ]. This study was limited to the population of Shanghai, China.…”
Section: Discussionmentioning
confidence: 99%
“…Six of thirteen selected features were comorbid chronic diseases. Our previous study had shown that comorbid chronic diseases was associated with greater probability of anxiety and depression (26), which indicating that physical problem might had great in uence on CSs' psychological health, and effectively monitoring and management of CCDs should be provided for CSs to address the psychological and psychical problems. Social support was another important predictor of CAD.…”
Section: Discussionmentioning
confidence: 98%
“…Having a chronic condition, such as diabetes, requires extensive self‐management, similar to cancer. It is possible that as the number of chronic conditions increases, patients’ risk for depression increases due to the stressors associated with disease management 48,56 . Moreover, those with multiple conditions exhibit a significant decline in physical functioning, limiting interpersonal and social activities 57 .…”
Section: Discussionmentioning
confidence: 99%